Pharmacognostic Evaluation of Prishniparni-Desmodium Gangeticum (Linn.) DC. - Aswathy , Krishna r; Ansary, P Y; Oommen, Sara Monsy; Shincymol, V V (International Research Journal of Ayurveda & Yoga, 2022)
Prishniparni –Desmodium gangeticum (Linn.) DC. is a well-known drug extensively discussed in the Ayurvedic classics. The plant and the therapeutical potential of its root is highly emphasized in the literature. Pharmacognosy is the study of crude drugs of plant and animal origin based on macroscopic and microscopic examination for the authentication and quality control. In present study, macroscopic and microscopic evaluation of root, was performed. Powder macroscopy as well as microscopy of powder of the drug was conducted. Assessment of colour, texture, odour and taste of powder were done in powder macroscopy. The macroscopic features of root, such as size, shape, external characters, type of fracture, colour, odour and taste were analysed. In microscopic evaluation of root, the different types of cells, their arrangement and cell contents were observed. The presence of cell constituents like prismatic calcium oxalate crystals, starch grain, stone cells, cork cells and fibres etc in the powder was observed using powder microscopy.